Visualization of Modern Political Space: Research Priorities - M. G. Goguadze (Проблемы постсоветского пространства, 2020)
In modern humanitarian studies and research in a number of social sciences, interpretation of visual data is often used. However, in some cases, it is able to make a negative adjustment in the methodology and research methods, which is a consequence of the terminological and theoretical underdevelopment of the theory of visuality itself, including within the framework of political science. The development of a general visual paradigm is currently in its infancy and is being carried out through the formation of the corresponding categorical apparatus, adequate to the real processes that it signifies.In political science studies, the theory of visibility is an innovation, since they lack the basic conceptual principles of the theory of visual political communication, which are not in demand due to the textual orientation of political science, which has for a long time linguistic-political bias, obscuring the whole complex of images in politics. However, the transformation of existing formats of rapidly developing political communication processes and technologies in the modern information society and the creation of new ones is carried out in the direction of increasing the amount of visual information that not only complements verbal forms, but also dominates the processes of political practices. The communication processes that ensure the functioning of political institutions are, in most situations, visually attributed and focused not so much on speech and audio as on visual techniques, which suggests that they are the main tool of political communication and a means of constituting political reality.